Equity across the cancer care continuum for culturally and linguistically diverse migrants living in Australia: a scoping review - Brighid Scanlon; Mark Brough; David Wyld; Jo Durham (BMC, 2021)
Abstract International evidence suggests migrants experience inequitable access, outcomes and treatment quality across the cancer care continuum. There is currently limited research assessing equity across the cancer care continuum for culturally and linguistically diverse migrants living in Australia. A detailed protocol and search strategy were developed and used to identify all relevant literature, utilising the Joanna Briggs Institute Reviewer's Manual. Systematic searching was conducted via multiple databases and identified studies were screened against pre-identified inclusion and exclusion criteria. 71 studies met the inclusion criteria for analysis. Most studies examined cancer detection via screening. Very few studies examined cancer prevention, diagnosis, treatment or palliative care. Most studies focused on patient-sided barriers to care and there was a paucity of information regarding institutional barriers to health. Cancer-related outcomes were seldom examined, and most studies were qualitative or behavioral analysis. Results highlighted significant communication issues spanning the cancer care continuum and a context of inadequate support for both patients and clinicians. There is a demonstrable need to examine equity in access and outcomes for culturally and linguistically diverse cancer populations. This requires the identification of cancer-related disparities and an examination of institutional barriers to care. Through addressing this dearth of information, future research and health policy can support the operationalisation of health equity.